Sampling efficiency of a polyurethane foam air sampler: Effect of temperature - Qiu-Liang Cai; Cen-Yan Huang; Lei Tong; Ning Zhong; Xiao-Rong Dai; Jian-Rong Li; Jie Zheng; Meng-Meng He; Hang Xiao (Environmental Science and Ecotechnology, 2024)
Effective monitoring of atmospheric concentrations is vital for assessing the Stockholm Convention's effectiveness on persistent organic pollutants (POPs). This task, particularly challenging in polar regions due to low air concentrations and temperature fluctuations, requires robust sampling techniques. Furthermore, the influence of temperature on the sampling efficiency of polyurethane foam discs remains unclear. Here we employ a flow-through sampling (FTS) column coupled with an active pump to collect air samples at varying temperatures. We delved into breakthrough profiles of key pollutants, such as polycyclic aromatic hydrocarbons (PAHs), polychlorobiphenyls (PCBs), and organochlorine pesticides (OCPs), and examined the temperature-dependent behaviors of the theoretical plate number (N) and breakthrough volume (VB) using frontal chromatography theory. Our findings reveal a significant relationship between temperature dependence coefficients (KTN, KTV) and compound volatility, with decreasing values as volatility increases. While distinct trends are noted for PAHs, PCBs, and OCPs in KTN, KTV values exhibit similar patterns across all chemicals. Moreover, we establish a binary linear correlation between log (VB/m3), 1/(T/K), and N, simplifying breakthrough level estimation by enabling easy conversion between N and VB. Finally, an empirical linear solvation energy relationship incorporating a temperature term is developed, yielding satisfactory results for N at various temperatures. This approach holds the potential to rectify temperature-related effects and loss rates in historical data from long-term monitoring networks, benefiting polar and remote regions.